Research Trends of Pre-Service Physics Teachers’ Critical Thinking Skills During 2001 to 2022 - Binar Kurnia Prahani; Hanandita Veda Saphira; Budi Jatmiko; Dwikoranto Dwikoranto; Tan Amelia; Muslimin Muslimin; Lutfhi Abdil Khuddus; Lindsay N. Bergsma (International Journal of Emerging Research and Review, 2023)
Objective: This research tends to visualize the trend research of PsPT CTS between 2001 and 2022. At the same time, no previous study has used bibliometrics to analyze the PsPT CTS in higher education. The main implication of this research are to find the novelty of the PsPT CTS research to increase their ability to teach physics critical thinking to students. Method: This research is a bibliometric analysis using Scopus as the primary metadata source. The document analyzed is a document between 2001 and 2022 or the last twenty years. Results: The trend of PsPT CTS tends to be interesting to future research, building upon the increase in the publication in PsPT CTS each year. The conference paper is the most used type of document in PsPT CTS due to its practice. It has a more visible impact since it is shown at a conference for many specialists from several disciplines to observe. The most widely used language in PsPT CTS publications is English due to it flexibility of readers around the world to have a good grip of the paper. For future research, it is still possible to develop or improve the obstacle PsT. Specifically, integrated STEM to enhance PsPT CTS due to its minimal keywords. Novelty: One of the 21st-century components is critical thinking, the trend of critical thinking research has become an exciting topic in the era of society 5.0. Therefore, to improve and develop the movements of critical thinking, especially in physics, an effort must be made.